2021
DOI: 10.3390/cells10030552
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of Ex Vivo-Generated Red Blood Cells Investigated by Optical Tweezers and Digital Holographic Microscopy

Abstract: Ex vivo-generated red blood cells are a promising resource for future safe blood products, manufactured independently of voluntary blood donations. The physiological process of terminal maturation from spheroid reticulocytes to biconcave erythrocytes has not been accomplished yet. A better biomechanical characterization of cultured red blood cells (cRBCs) will be of utmost interest for manufacturer approval and therapeutic application. Here, we introduce a novel optical tweezer (OT) approach to measure the def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 52 publications
(61 reference statements)
1
12
0
Order By: Relevance
“…After placement on the cell body, large moving EVs could be recaptured by the laser trap (Table 1, n = 10/10), proving that they were outside neurons, whereas only 27% of ‘static’ EVs, that remained adherent to the place of delivery, were recaptured by optical tweezers, being transiently attracted towards the laser (Table 1, n = 4/15). Although we could not exclude that the laser trapping force (maximum 50 piconewton for our setup) might not be able to re‐trap EVs strongly adhering to the neuron surface (Ashkin, 1992; Bernecker et al., 2021), this suggested that a fraction of large EVs may undergo internalization into the neuron cell body. To assess this hypothesis, we labelled large EVs with the fluorescent dye mCLING (Brenna et al., 2020) and analysed by confocal microscopy the localization of mCLING‐labelled large EVs 1 h after in bulk addition to neurons transfected with membrane‐targeted GFP.…”
Section: Resultsmentioning
confidence: 97%
“…After placement on the cell body, large moving EVs could be recaptured by the laser trap (Table 1, n = 10/10), proving that they were outside neurons, whereas only 27% of ‘static’ EVs, that remained adherent to the place of delivery, were recaptured by optical tweezers, being transiently attracted towards the laser (Table 1, n = 4/15). Although we could not exclude that the laser trapping force (maximum 50 piconewton for our setup) might not be able to re‐trap EVs strongly adhering to the neuron surface (Ashkin, 1992; Bernecker et al., 2021), this suggested that a fraction of large EVs may undergo internalization into the neuron cell body. To assess this hypothesis, we labelled large EVs with the fluorescent dye mCLING (Brenna et al., 2020) and analysed by confocal microscopy the localization of mCLING‐labelled large EVs 1 h after in bulk addition to neurons transfected with membrane‐targeted GFP.…”
Section: Resultsmentioning
confidence: 97%
“…Cell membrane fluctuation analyses showed high CMF similarities between nRBC, nRET and cRBC lipids , while CMF is different for cRBC w/o lipids . However, this value is affected by the spherical shape of the cell and its height, as discussed in our recent publication (Bernecker et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…Cell morphology and cell membrane fluctuations (CMF) were measured for RBC in physiological solution, with the cells placed on a coverslip, using a custom DHM system based on a Mach-Zehnder interferometer ( Bernecker et al, 2021 ). The morphological parameters: area, volume and sphericity were calculated from the cell height map as described ( Bernecker et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a combination will allow investigating the morphological changes occurring to bio-samples in their natural environment, obtaining sample features otherwise inaccessible using optical tweezers, like sample volume, surface area, shape, and thickness fluctuations. Two-beam interferometer geometry has been reported for combining optical tweezers and digital holographic microscopy 25,[43][44][45] .…”
Section: Introductionmentioning
confidence: 99%